2011
DOI: 10.1162/jocn.2010.21557
|View full text |Cite
|
Sign up to set email alerts
|

Alpha Oscillations Correlate with the Successful Inhibition of Unattended Stimuli

Abstract: Because the human visual system is continually being bombarded with inputs, it is necessary to have effective mechanisms for filtering out irrelevant information. This is partly achieved by the allocation of attention, allowing the visual system to process relevant input while blocking out irrelevant input. What is the physiological substrate of attentional allocation? It has been proposed that alpha activity reflects functional inhibition. Here we asked if inhibition by alpha oscillations has behavioral conse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

37
323
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 418 publications
(362 citation statements)
references
References 45 publications
37
323
2
Order By: Relevance
“…We found that decreases in α-activity during the decision period correlated with task performance in S1, S2, DPC, MPC-left, and M1. The current findings are consistent with previous work showing that somatosensory α-activity influences discrimination performance (18,27) and with the visuospatial attention literature linking α-activity to detection performance (15)(16)(17). These previous findings have resulted in the notion that α-activity is involved in sensory gating.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We found that decreases in α-activity during the decision period correlated with task performance in S1, S2, DPC, MPC-left, and M1. The current findings are consistent with previous work showing that somatosensory α-activity influences discrimination performance (18,27) and with the visuospatial attention literature linking α-activity to detection performance (15)(16)(17). These previous findings have resulted in the notion that α-activity is involved in sensory gating.…”
Section: Discussionsupporting
confidence: 92%
“…In particular, α-activity might serve to shape the state of sensory brain regions to direct the flow of information and optimize performance (8). In support of this idea, several studies on visual perception have shown that anticipatory α-activity reflects the orienting of attention (9)(10)(11)(12)(13)(14) and influences detection performance (15)(16)(17). Recently, it was shown that the functionality of α-oscillations can be generalized to the somatosensory system (18)(19)(20)(21).…”
mentioning
confidence: 94%
“…Further, it is in line with results from the visual domain: higher ongoing visual alpha activity has been related to lower visual detection performance van Dijk et al, 2008). Furthermore, alpha lateralization over parieto-occipital regions has been correlated with detection of attended and successful inhibition of unattended visual stimuli (Thut et al, 2006;Händel et al, 2011). Recent TMS studies entraining posterior alpha oscillations strongly suggest that the influence of alpha activity on perception is causal rather than merely correlational (Sauseng et al, 2009;Romei et al, 2010).…”
Section: Alpha Lateralization Required For Optimal Performancesupporting
confidence: 82%
“…In visual spatial attention tasks, alpha activity shows a lateralized pattern: alpha decreases contralateral to the attended location (Sauseng et al, 2005) and increases contralateral to the ignored location, presumably to suppress distracting input (Worden et al, 2000;Kelly et al, 2006). This lateralized alpha activity correlates with visual detection performance (Thut et al, 2006;Händel et al, 2011). The functionality of alpha might be generalized to other modalities.…”
Section: Introductionmentioning
confidence: 96%
“…This could be convincingly pointed out by its left-lateralized activity pattern irrespective of response-hand laterality ( Figure 7A), and by the non-motor region in which it was generated, namely, the LOT Noteworthy, a recently proposed framework postulates that alpha activity reflects functional inhibition (Jensen and Mazaheri, 2010). This interpretation was derived from reports of alpha power suppression in task-engaged brain areas (van Gerven and Jensen, 2009;Handel et al, 2010), and alternatively of alpha power enhancement in non-engaged areas (Haegens et al, 2010). Thus, alpha suppression as observed here could be indicative of the functional engagement of the LOT as a selective activation pattern gating fully conscious perception of words.…”
Section: Scalp Topographies and Brain Views (Sagittal And Axial Planementioning
confidence: 63%